Die Fingerendgelenkversteifung mit der Doppelgewindeschraube - Spies, Christian; Unglaub, Frank (Operative Orthopädie und Traumatologie, 2017)
ObjectiveArthrodesis of the distal interphalangeal joint of the fingers and interphalangeal joint of the thumb in order to gain reliable stability and function.IndicationsPrimary and secondary osteoarthritis, rheumatoid arthritis, defect lesions, septic joint destruction, posttraumatic joint deviation, fatal joint instability, fatal tendon lesions.ContraindicationsPersistent infections (empyema, osteomyelitis, phlegmon), deficient soft tissue mantle, bone/screw mismatch.Surgical techniqueUsing Beasley’s approach the extensor tendon is identified and sectioned. Incision of the collateral ligaments enables good exposition. Precise resection of the joint surfaces. An orthograde guidewire is place into the distal phalanx. After adjustment of the arthrodesis which is controlled using x‑ray, the guide wire is drilled into the middle phalanx in retrograde fashion. An adequate headless compression screw is introduced via a transverse incision at the fingertip using the guide wire, the former screw is placed until sufficient compression is generated.Postoperative managementFinger splint reaching to the proximal interphalangeal joint for 4 weeks after arthrodesis, full weight bearing after 6 weeks.ResultsSeventeen patients were examined after arthrodesis of the distal interphalangeal joint using the headless compression screw. The arthrodesis proved to be reliable and safe with a low complication rate and a good functional outcome. The modified Mayo Wrist Score (MMWS) was on average 89 (range 55-100); the outcome parameter DASH (disabilities of arm, shoulder and hand) score was on average 27 (range 1-60).
Englische Zusammenfassung unter dem Titel: Arthrodesis of the distal interphalangeal joint using the headless compression screw
Gesehen am 28.08.2018